Hegemonic Culture and Subaltern: A Compromised Veil in Indonesian Islamic Popular Novel - Tami, Rosmah; Faruk, Faruk; Adi, Ida Rochani (Lingua Cultura, 2017)
This research was based on the powerful function of the aesthetics in the society. Novel as an art work also functioned as an arena in which ideologies contest and negotiate. The research intended to show a mechanism underlining novel to have a significant hegemonic role. The material object was taken from Islamic popular novel namely â€œKetika Mas Gagah Pergi dan Kembaliâ€. The formal object was the negotiation of ideology which focused on the contact between intellectual and subaltern leading to the formation of a new compromised cultural practice. By applying the theory of hegemony in discussing the contestation and negotiation of ideologies in the novel, it is found that the contestation and negotiation between hegemonic and subaltern ideology lead to the occurrence of a compromise between the interest of the intellectual and the subaltern. The interest of the subaltern is based on the nostalgia of the past and fear or uncertain condition of future which lay in the domain of imagination that structures the novel.